The revitalization of Mak Yong in the Malay world - MPSS, Pudentia (UI Scholars Hub, 2010)
Culture can only be revitalized when a cultural tradition is considered of significant importance by its owning community. How important it is for the identity of that community or in how far it symbolizes that community can only be established after in-depth study. It is crucial that revitalization activities involve the community. If not, efforts would be pointless. Mak Yong is one of the Malay performing art traditions that has been revitalized over the last five years. It is an art form that originates in southern Thailand and was brought to Bintan in the Riau Islands (Kepulauan Riau, Kepri) via Singapore. It combines dialogue, dance, singing, music, and stories and may still be found in the Riau Islands in Indonesia. It is interesting to show how Mak Yong has represented and expressed Malay dynamics by means of revitalizations efforts.